The impact of the Bolsheviks Revolution on the political development and system of government of the new state of the 20th century - Guslin, Guslin; Octavian, Amarulla (Political Science Program, Universitas Negeri Semarang, 2021)
The Bolshevik Revolution forced the end of Tsar Nicholas II's imperial rule in Russia. Furthermore, under the leadership of Vladimir Lenin, Russia formed a new government in the form of the Republic. The main power of this government is entirely under the Dictatorship of the Proletariat. Subsequent changes in the form of government in Russia, especially after World War I, inspired newly independent countries in the mid-20th century to follow the same system of government. Through theories about the state, politics, and government system, this study will analyze the influence of the Bolshevik revolution on the new system of government for new countries in the world in the 20th century. To analyze the effect of changes in the form of government, the authors use an exploratory qualitative research method with a historical approach through a literature study. After the Revolution, based on a common view of colonialism, human rights, ideology, and the strong understanding of Marxism-Leninism, several countries in the world that were newly independent in the mid-20th century were inspired by the Bolshevik Revolution by forming countries with a Republican system of government, including Indonesia.